Bicultural peace pedagogy: opportunities and obstacles - Standish, Katerina (Frontiers in Research Metrics and Analytics, 2024)
This article appreciates decolonization in education, positing bicultural pedagogy as peace pedagogy. It will encapsulate peace education, peace pedagogy, colonization, Indigenous rediscovery, and Indigenization of the curriculum (biculturalism) and then turn to the transformative practice of decolonization in education. The paper seeks to propose a conceptual bridging facet from five core Māori values: wairuatanga, manaakitanga, kotahitanga, whanaungatanga, and rangatiratanga, to Indigenous pedagogy and, finally, to peace pedagogy. The alignment of Indigenous pedagogy and peace pedagogy is an attempt to evaluate the potential of bicultural peace pedagogy as a decolonizing education. The paper finds congruence between Western peace pedagogy and several gaps related to practice and cultural goals. To assist other non-Indigenous knowledge workers (termed Pākehā in Aotearoa/New Zealand) in decolonizing education, this paper has sought to elevate aspects of peace culture that align with Indigenous practices/values.